Pemberdayaan Guru Madrasah Diniyah Al-Rachmat: Efektifitas Pelatihan Desain Grafis Untuk Digitalisasi Dakwah Di Media Sosial - Fakhridana, Farhan Muzakki; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The graphic design training aims to empower teachers of Madrasah Diniyah Al-Rachmat in creating digital da'wah media on social media. Although many teachers have not mastered graphic design techniques, training with a training approach with intensive mentoring shows positive results. The results of the analysis of graphic design skills before and after training showed a significant improvement, with the average score increasing from 51.7 to 72.3. Two young teachers recorded the highest scores, while senior teachers showed moderate progress. This training is effective in improving technical competence and teacher confidence, and can be extended to other madrasah institutions to digitize da'wah on social media.